Dependency, White Privilege, and Transnational Hegemonic Reconfiguration: Investigating Systems of Power and Identity Privilege in The Bahamas - David Allens (Caribbean Studies Students' Union, 2020)
White cultural hegemony has been used as a determinant of identity privilege in The Bahamas since the beginning of British colonialism. This ideal justifies and confers the dominance of whiteness while also including a moral responsibility to enforce the racial hierarchy as a part of a "global cognitive dysfunction" (Mills 18) that sees non-white actors as intrinsically lesser; an understanding Charles Mills argues is needed to uphold a racialized social contract. This "grammar of racial difference" inculcates the need for whiteness to act as savior through the subjugation and cultural integration of the "other" (Mahmud). However, beyond its role as a dysfunction, this conception of a moral obligation-or colloquially, a 'white savior complex'-guides understandings of why colonial leaders forged hegemonic relationships with the U.S. despite the country's apparent intent to achieve independence. These relationships were a strategic part of a colonial-savior complex and adherence to a global system that values 'whiteness.'  This paper suggests that despite independence, The Bahamas remains subjected to the dependency role under a system of white privilege, resulting from colonial agreements made with the United States, and multi-national agencies, and regulatory bodies that enforce a hegemonic reconstruction of influence. Ergo, the cultural hegemony of the United States as an industrialized giant merely filled the void that the British rule left behind.